The Implementation Of Interviewing Technique To Increase Students Speaking Ability By Online Class At The Tenth Grade Students Of SMA Negeri 4 Parepare - Ismail (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
Interviewing technique was attractived technique to implement on English learning process specially in speaking field of the students that still low, caused of teachers teachnique that made students less of self-confidence and doesn’t actively in learning process. It was proved based on the students achievment in researchers observatioan data which was showed that their speaking ability was still low. Therefore, the objective of this research was to find out whether or not the implementation of interviewing technique can increase students speaking ability at the tenth grade students of SMAN 4 Parepare in online class by using whatsapp group as a teaching media. The researcher applied pre-experimental class design with one group pretest and posttest design. The population of this research was tenth grade students of SMAN 4 Parepare academic year 2020/2021. The sample of this research was taken by using purposive sampling which was class X MIPA 3 that consisted of 20 students as a samples. The result of data analysis showed that the students speaking ability was increased. It was proved by the mean score in pretest was 56,3 while the mean score in posttest was 80,95. So, the score of t-test 2,217 was greater than t-table th degree of freedom (df = n − 1) 19 for 0,05 level of significance. It can be said that the implementing of interviewing technique increased the students speaking ability at the tenth grade students of SMAN 4 Parepare.